PERILAKU DINAMIK PELAT PERKERASAN KAKU JALAN RAYA AKIBAT BEBAN LEDAKAN SETEMPAT - Priono, Anjas Budi; Alisjahbana, Sofia Wangsadinata (Universitas Tarumanagara, 2020)
In structural and transportation engineering applications, the dynamic response of orthotropic plates is an essential matter. Rigid pavement plates are generally designed as orthotropic plates which have unequal stiffness in two perpendicular directions Engineers did not consider the effects of dynamic loads such as those from machine vibrations or blast load. Dynamic analysis of rigid pavement plates due to local blast loads on concrete slabs in this research is modeled as concrete slabs with boundary condition that every edges of plates have a dowel-tie bar support and The rigid concrete pavement sitting on elastics Pasternak foundation is modeled by using the Kirchhoff theory of thin plates. Pasternak foundation have elastic vertical spring support and continuous shear layer. The main system responses that are observed are the transversal deflections at midspan and the internal stresses of the plate, particularly the maximum principle stress, minimum principle stress and maximum shear stress. Three loading phases are included in the analysis, namely: the positive phase, the negative phase, and the free vibration phase. Analyses are carried out utilizing a numeric approach termed the Modified Bolotin Method with two trancedental equation. The analysis is performed when the load is above the plate (0 ≤ t ≤ t0). Deflection from various load positions on the set of slab models throughout all three phases are then compared side-by-side. Bending moment, shear forces, and stresses are calculated on all slab models with the Friedlander localized blast loading applied at midspan and the results are presented as stress contours that are then compared between each model. The results showed that the largest structural dynamic response occurred in the free vibration phase, not in the positive phase or the negative phase. Reduction of deflection and bending moment based on the most significant effect, plate thickness is the first followed by the effect of explosion position if it occurs further to edge of plate, and latest is adding supporting stiffness soil layer. Keywords: dowel and tie-bar; Localized blast load; Modified Bolotin Method; Pasternak foundation; Rigid PavementABSTRAKDalam aplikasi rekayasa struktur dan teknik transportasi, respons dinamik pelat ortotropik adalah masalah penting. Pelat perkerasan kaku jalan raya umumnya didesain sebagai pelat ortotropik yang memiliki kekakuan yang tidak sama dalam dua arah yang saling tegak lurus. Pelat perkerasan kaku jalan raya sering kali didesain oleh para insinyur tidak memperhitungkan efek dari beban dinamik lain seperti beban yang berasal dari getaran mesin atau ledakan. Analisis dinamik pelat perkerasan kaku jalan raya akibat beban ledakan setempat di atas pelat beton dalam tesis ini dimodelkan sebagai pelat beton dengan kondisi semua tepi pelat beton memiliki tumpuan dowel – tie bar dan di atas media tanah dengan model pondasi Pasternak dari teori Kirchoff-Love mengenai pelat tipis. Pondasi Pasternak memiliki dukungan pegas vertikal elastis dan lapisan geser menerus di bawahnya. Respons sistem yang diamati adalah lendutan transversal pada tengah bentang dan tegangan dalam pada pelat, khususnya tegangan utama maksimum, tegangan utama minimum dan tegangan geser maksimum. Tiga tahap beban disertakan dalam analisis, yaitu fase positif, fase negatif dan fase getaran bebas. Analisis dikerjakan dengan pendekatan numerik yang disebut Modified Bolotin Method dengan bantuan dua persamaan transendental. Analisis dilakukan ketika beban berada di atas pelat (0 ≤ t ≤ t0). Lendutan dari beberapa posisi beban dari tiga tahap dibandingkan. Momen lentur, gaya geser, dan tegangan dihitungkan pada semua model dengan letak beban setempat Friedlander di tengah bentang. Nilai tegangan disajikan dalam bentuk grafik kontur yang dapat dibandingkan antara setiap model. Hasil penelitian menunjukkan respons dinamik struktur terbesar terjadi pada fase free vibration, bukan pada fase positif maupun fase negatif. Pengurangan lendutan dan momen lentur apabila ditinjau berdasarkan pengaruh paling singnifikan, ketebalan pelat adalah urutan pertama diikuti pengaruh posisi ledakan apabila terjadi makin ke tepi pelat, dan terakhir penambahan kekakuan lapisan tanah pendukung.